Clinical and genetic spectrum of inborn errors of immunity: a retrospective study on outcomes at a single center - Kose, Hulya; Akalin, Akcahan (Frontiers in Immunology, 2026)
IntroductionInborn errors of immunity (IEI) are particularly prevalent in regions with high rates of consanguinity, yet the genetic profiles in these populations are underreported. This study aims to describe the clinical and molecular characteristics of IEI in a highly consanguineous population and investigate the impact of genetic diagnosis on patient management.MethodThis retrospective study included 52 patients with suspected IEI, as defined by the IUIS criteria. Clinical, immunological, and demographic data were recorded. Genetic analyses were performed primarily using next-generation sequencing (NGS) gene panels, and all pathogenic variants were confirmed by Sanger sequencing. Variants were interpreted in accordance with the ACMG guidelines.ResultsA total of 52 patients were included in the study, with 92% of the individuals born to consanguineous parents, comprising 28 females and 24 males. The mean age at diagnosis was 4.63 ± 2.5 years. The median duration of follow-up was three years. The overall incidence was 0.3% representing the proportion of patients diagnosed with IEI among those referred to our center during the study period. A high rate of consanguineous marriage was observed, reported in 92% of the cases. The most frequently represented category was Predominantly Antibody Deficiencies (PAD), accounting for 20 patients (38.5%), including 12 cases (23%) of transient hypogammaglobulinemia of infancy (THI) and 7 cases (13%) of selective IgA deficiency. Among the 52 patients, 3 (5.8%) were diagnosed with severe combined immunodeficiency (SCID): 1 patient had ADA deficiency, and two patients had DNA ligase IV deficiency (LIG4). Additionally, 14 patients (26%) were diagnosed with combined Immunodeficiencies (CID). Thirty patients were treated with IVIG, and 3 patients underwent HSCT. A molecular diagnosis was established in 33 patients (63%). Genetic findings influenced clinical management in 82% of variant-positive cases, including decisions regarding HSCT, targeted therapy, and genetic counseling.ConclusionThis study highlights the distinctive genetic characteristics of IEI in a population with high consanguinity, emphasizing the need to incorporate molecular diagnostics into standard immunology practice, particularly in areas where recessive disorders are prevalent.